OPTIMIZATION OF FRACTAL COMPRESSION OF 3D IMAGES USING A GENETIC ALGORITHM - Zahra Khanmirza (Advances in Science and Technology Research Journal, 2015)
3D image technologies are widely recognized as the next generation of visual presentation considering the achievement of more natural experiences. To produce such images, two cameras are placed in a bit different position. When we seek to compress such images, we need a procedure to compress two images synchronously. In this paper, a procedure is presented for a suitable compression based on fractal compression which shows that we obtain high compression rate with an appropriate image quality; however, since the proposed procedure has a low search speed, we used genetic algorithm to remove the case.